The transformation of household expenditure from offline to online: The case of South Korea - Dong Hee Lee; Duk Hee Lee (International Telecommunications Society (ITS), 2010)
Using longitudinal time-series data, this paper analyzes the causes of the recent sharp increase in household expenditure on telecommunications in South Korea with a linear approximate almost ideal demand system (LA/AIDS) model. The main results are as follows. First, Korean household demand for telecommunications is income elastic and price inelastic following structural changes associated with the rapid diffusion of mobile phones and the Internet during 1998-2007. Second, following these structural changes, telecommunications have become substitutes for books and printed matter and culture & recreational durable goods and they complement cultural & recreational services and private education. This suggests that the pattern of household expenditure has changed from offline to online, and this helps explain the increase in the price elasticity and the expenditure on telecommunications in Korea. While the increase in telecommunications expenditure is a natural phenomenon representing structural changes to the information society, the increase may also cause a delay in the diffusion of new services and broaden the digital divide. Consequently, this paper provides some implications for planning a more desirable and forward-looking policy to prepare for the future information society.
Keywords: D12; L86; L96; 330; Telecommunications expenditure; Online activity; Almost Ideal Demand System; Demand elasticity; South Korea